Geographic Information System for Customer Distribution in PT. Dinamika Lubsindo Utama Using the Haversine Algorithm - Setiawan, Bagus; Samsudin, Samsudin (Teknik Informatika Universitas Pamulang, 2023)
This research was conducted because the distribution of customers who do not have accurate location information results in couriers who will deliver products often traveling long distances to get to the location of customers who make orders because they repeat routes that have been taken previously. The research problem formulation revolves around implementing the Haversine algorithm for calculating the distance between the courier's location and the customer's order location. Additionally, it focuses on designing and constructing a geographic information system for customer distribution, utilizing the Android-based Haversine algorithm. The research method used is Research & Development where researchers will collect information first and develop the system to be built. For system development, the Waterfall method is used. To calculate the distance from the courier's location to the customer's ordering location, the Haversine algorithm is used. From this research, the results obtained are a geographic information system that will provide information on customers who ordered on that day as well as the distance from the courier's location to the location of the customer who made the order using the Android-based Haversine algorithm. The conclusion of this research is that the geographic information system that is built will be able to assist couriers in delivering products to customers who make orders that day. Because the system will sort the customer's location from closest to furthest so that the courier will not repeat the route he has previously taken, making it more effective.